PENGELOLAAN RISIKO DALAM MENGAHDAPI TANTANGAN ERA DIGITAL PADA LEMBAGA PENDIDIKAN (penelitian di SMK Al-Hadi) - Khoiriyah, Nurdika; Hidayat, Wahyu (Muttaqien Publsihing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2024)
Risk management is a critical approach in recognizing, evaluating and managing potential risks that may occur, especially in various sectors, including the education sector. The risk management approach requires careful planning, implementation of appropriate policies, and active involvement of all stakeholders with open communication. The primary strategy for facing challenges in the digital era involves training teaching staff in technology, developing a curriculum integrated with digital content, and administrative risk management. As a complex environment involving various parties, schools have risks that must be managed carefully to ensure the safety and welfare of students. This research uses qualitative methods by obtaining information through interviews with one public relations staff at Al Hadi Vocational School and referring to various literature. This research aims to understand risk management and the challenges Al Hadi Vocational School faced in Bandung in the digital era. The study results show that Al-Hadi Vocational School has implemented digitalization in schools by involving all educators expected to master technology. This digitalization is carried out to support effective teaching and minimize risks in ensuring student safety and welfare.